Distribution of endangered Italian gudgeon Romanogobio benacensis (Cypriniformes, Cyprinidae, Gobioninae) with remarks on distinguishing morphological characters - Dušan Jelić; Mišel Jelić; Petar Žutinić; Ivana Šimunović; Primož Zupančič; Alexander M. Naseka (ZooKeys, 2018)
Distribution data on many freshwater fish species in Croatia are scarce and species identifications are difficult, requiring further detailed studies. This paper presents a report of the Italian gudgeon Romanogobio benacensis from the Mirna River in the Istra Peninsula in Croatia, in the south-east from its previously known distribution range. The identification of R. benacensis in Croatia was supported by a morphological comparison with R. benacensis from Italy and Slovenia, the common gudgeon Gobio gobio, and the Danubian gudgeon Gobio obtusirostris from geographically close locations. A combination of character states (number of scales between anus and anal-fin origin, branched pectoral-fin rays, lateral-line scales, total, abdominal, and caudal vertebrae, and the size and number of lateral blotches) distinguishes R. benacensis from both G. gobio and G. obtusirostris. The phylogenetic analyses using mitochondrial sequences of cytochrome b gene confirmed that specimens from the Mirna River belong to R. benacensis. Also, Reka River system (Adriatic Sea basin) in Slovenia is inhabited by a possibly introduced Danubian gudgeon, G. obtusirostris, and not by R. benacensis.